The Relationship between Willingness to Communicate, Locus of Control and Foreign Language Anxiety among Iranian EFL Learners - Farzaneh Ehsani; Qotboddin Jan-nesar Moghaddam (Iranian Evolutionary Educational Psychology Journal, 2021)
This study started with the aim of exploring the relationship between willingness to communicate (WTC), foreign language anxiety (FL anxiety) and locus of control (LOC) among Iranian EFL learners. To conduct this study, a correlation-descriptive design was selected to achieve the objectives. The participants consisted of 80 intermediate male and female EFL learners randomly selected from among EFL students studying in different branches of Ibne Sina Language institute, Iran. At the beginning, the participants were asked to fill Rotter's (1966) Locus of Control Scale. One week later, Willingness to Communicate (WTC) Questionnaire was given to the participants to be filled by them. One week after that, the researcher gave FL Anxiety Questionnaire to the participants and asked them to fill it. The collected data were analyzed using descriptive statistics and Pearson Product-moment correlation test. The results showed that there was no relationship between WTC and LOC among Iranian EFL learners; there was a significant but negative correlation between WTC and FL anxiety; and LOC and FL anxiety were not significantly correlated.